Pengembangan Indirect Dipstick ELISA untuk Deteksi Aflatoksin B1 pada Pakan dan Jagung - Sri Rachmawati; Prima Mei Widiyanti; Hasim Munawar (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2013)
Enzyme Linked Immunosorbent Assay (ELISA) is an immunological method can be used to analyze aflatoxin B1 (AFB1) in feed. ELISA technique must be done by using an instument (ELISA reader) which is not effective when used in the field. Therefore, the simple ELISA technique is needed such as indirect dipstick ELISA (d-ELISA). The aim of research is to develop AFB1 screening method using   d-ELISA. The research is focusing on  development and validation of indirect d-ELISA, and its application on sample of feed and corn. The results showed that the best coating time for antigen AFB1-BSA (0,4 ug/ml) is 24 hours, reaction time for antibody anti AFB1 (1/800) and AFB1 standard is 15 minutes, and reaction time for goat anti rabbit-HRPO conjugate 1/2500 and substrate of orthodiasianin (ODN) is 20 minutes. The results of indirect d-ELISA on 22 samples are found that 7 samples are contaminated by AFB1 with concentration above 20 ng/g and 7 samples are contaminated by AFB1 with concentration in the range of 0 – 20 ng/g. Finally, it is concluded that the indirect d-ELISA is applicable to be used in the fields.